Ascites and Encapsulating Peritonitis in Endometriosis: a Systematic Review with a Case Report - Magalhães, Thais Fontes de; Augusto, Kathiane Lustosa; Mota, Livia Ponte; Costa, Arthur Ribeiro da; Puster, Rainardo Antonio; Bezerra, Leonardo Robson Pinheiro Sobreira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Endometriosis can have several different presentations, including overt ascites and peritonitis; increased awareness can improve diagnostic accuracy and patient outcomes. We aim to provide a systematic review and report a case of endometriosis with this unusual clinical presentation. The PubMed/MEDLINE database was systematically reviewed until October 2016. Women with histologically-proven endometriosis presenting with clinically significant ascites and/or frozen abdomen and/or encapsulating peritonitis were included; those with potentially confounding conditions were excluded. Our search yielded 37 articles describing 42 women, all of reproductive age. Ascites was mostly hemorrhagic, recurrent and not predicted by cancer antigen 125 (CA-125) levels. In turn, dysmenorrhea, dyspareunia and infertility were not consistently reported. The treatment choices and outcomes were different across the studies, and are described in detail. Endometriosis should be a differential diagnosis of massive hemorrhagic ascites in women of reproductive age.
Keywords: endometriosis; ascites; peritonitis; systematic review; treatment